The prevalence and impact of low faecal elastase-1 in community-based patients with type 2 diabetes. (October 2019) - Riceman, Michael D.; Bound, Michelle; Grivell, Jacqueline; Hatzinikolas, Seva; Piotto, Samuel; Nguyen, Nam Q.; Jones, Karen L.; Horowitz, Michael; Rayner, Christopher K.; Phillips, Liza K.
Abstract: Aims: To determine the prevalence of low faecal elastase-1 (FE-1) (≤200 μg/g) in type 2 diabetes (T2DM), and to test the hypothesis that pancreatic enzyme replacement therapy (PERT) would reduce postprandial glycaemia after a high-fat, high-carbohydrate meal in T2DM subjects with low FE-1. Methods: Of 109 community-based patients who submitted stool samples, 10 had low FE-1 and 8 were recruited (6 male, 2 female, 67.8 ± 3.0 years). Participants were given a high-fat, high-carbohydrate meal (718 kcal) with either pancrelipase (50, 000 units) or placebo in a randomised, double-blind, crossover fashion. The primary outcome was the difference in postprandial glycaemia following PERT vs placebo, as evaluated by the incremental area under the postprandial plasma glucose curve (iAUC). Secondary outcomes included differences in gastric half-emptying time (T50) measured using scintigraphy, and C-peptide iAUC. Results: The prevalence of low FE-1 in T2DM was 9.2% (95% CI 3.8–14.6%). There was no difference in postprandial glycaemia iAUC (P = 0.38), gastric emptying T50 (P = 0.69) or C-peptide iAUC (P = 0.25) after PERT compared to placebo. Conclusions: Decreased FE-1 has a relatively low prevalence in community-based patients with T2DM, and PERT does not reduce postprandial glycaemia in these patients. Clinical Trial Registration Number: ACTRN12617000349347.